Lactococcus garvieae: CHARACTERIZATION AND ABILITY TO INHIBIT THE GROWTH OF AQUACULTURE PATHOGENIC BACTERIA - Mawardi, Mira; Indrawati, Agustin; Lusiastuti, Angela Mariana; Wibawan, I Wayan Teguh (Agency for Marine and Fisheries Extension and Human Resources, 2024)
Lactococcus garvieae is a gram-positive ovoid cocci bacterium formerly classified as a member of the Lactococcus genus. This study aims to isolate L. garvieae from catfish rearing pond and characterize it as a potential probiotic candidate. L. garvieae was identified and characterized through phenotypic and genotypic observation, genomic % G C content analysis, cell surface hydrophobicity assays, acidification test, in vitro antagonism, and a profile of antimicrobial activities. The MT597595.1 accession number corresponds to L. garvieae, as determined by a molecular identification test. Biochemical characterization was performed using API 50 CH kit. The genomics %G C content of L. garvieae was 51.8. Findings from acidification ability tests, in vitro antagonism tests, and the ability of bacteria to grow in broth medium at pH 4 reveal that L. garvieae can inhibit the growth of Aeromonas hydrophila, Streptococcus agalactiae, Streptococcus iniae, and Edwardsiella ictaluri. However, it does not suppress the growth of L. garvieae Edwardsiella tarda. Remarkably, L. garvieae has the ability to reduce the pH of neutral broth medium turning it acidic. Furthermore, L. garvieae’s hydrophobic cell surface exhibited an adhesive, hydrophobic, and protein surface cell content with a compact growth pattern consistent with postive SAT and MATH assay. Antimicrobial activity tests, encompassing 11 antibiotics, disclosed resistance to Nalidixic acid while displaying intermediate sensitivity to Streptomycin and Trimethoprim. In conclusion, L. garvieae demonstrates an inhibitory effect on the growth of pathogenic bacteria, underlining its potential as a probiotic candidate.